2016
DOI: 10.1080/19345747.2016.1204639
|View full text |Cite
|
Sign up to set email alerts
|

Causal Connections Between Mathematical Language and Mathematical Knowledge: A Dialogic Reading Intervention

Abstract: The acquisition of early mathematical knowledge is critical for successful long-term academic development. Mathematical language is one of the strongest predictors of children's early mathematical success. Findings from previous studies have provided correlational evidence supporting the importance of mathematical language to the development of children's mathematics skills, but there is limited causal evidence supporting this link. To address this research gap, 47 Head Start children were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(162 citation statements)
references
References 66 publications
12
144
1
5
Order By: Relevance
“…In contrast, Napoli and Purpura (2018) found that the frequency with which parents read number story books to their children was related to numeracy performance. Number storybook reading may specifically support learning of math and spatial words such as before, lower, or most (Purpura, Napoli, Wehrspann, & Gold, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Napoli and Purpura (2018) found that the frequency with which parents read number story books to their children was related to numeracy performance. Number storybook reading may specifically support learning of math and spatial words such as before, lower, or most (Purpura, Napoli, Wehrspann, & Gold, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Home‐based studies demonstrate a cumulative effect of the amount of math talk that parents provide to their children (e.g., number talk as examined by Levine, Suriyakham, Rowe, Huttenlocher, & Gunderson, ), and parent talk about specific math concepts is predictive of children's abilities in the same areas of math (e.g., cardinality, Gunderson & Levine, ; spatial concepts, Pruden, Levine, & Huttenlocher, ). In addition to correlational support for a link between parent math language and children's math knowledge, there is also causal evidence of a link between math language and math knowledge (Purpura, Napoli, Wehrspann, & Gold, ). Importantly, there is substantial variation in the amount of parent math talk in the home, and family characteristics such as education and socioeconomic status (SES) appear to account for some of this variance (e.g., Levine et al., ; Saxe, Guberman, & Gearhart, ; Vandermaas‐Peeler, Nelson, Bumpass, & Sassine, ).…”
Section: Theoretical and Empirical Support For Home Numeracymentioning
confidence: 99%
“…To support parents' understanding of children's various numeracy abilities and children's subsequent numeracy development, researchers and interventionists should focus on exposing parents to the range of numeracy skills that exist, as well as various activities that promote these different components. For example, having storybooks that include age-appropriate mathematical language and concepts for children (e.g., Purpura, Napoli, et al, 2017)-along with how the concepts build upon each other, suggestions for activities to practice with children, and tips for knowing if their children understand the concept-may broaden parents' understanding of which mathematics skills are appropriate to introduce to their children. Further, parents should have an understanding of the developmental trajectories of children's numeracy skill development so they know how to support particular numeracy skills at certain developmental time periods.…”
Section: Supporting Parents' Increased Understanding Of Children's Skmentioning
confidence: 99%